Airborne lidar observations in the wintertime Arctic stratosphere - Ozone - Browell, E. V.; Ismail, S.; Carter, A. F.; Butler, C. F.; Fenn, M. A.; Kooi, S. A.; Tuck, A. F.; Toon, O. B.; Loewenstein, M.; Schoeberl, M. R. (1990)
Large-scale distributions of ozone (O3) were measured with an airborne lidar system as part of the 1989 Airborne Arctic Stratospheric Expedition. Measurements of O3 distributions were obtained between January 6 and February 15, 1989, on 15 long-range flights into the polar vortex from the Solar Air Station, Norway. The observed O3 distribution was found to clearly indicate the edge of the polar vortex and to be an effective tracer of dynamical processes in the lower stratosphere. On the last two flights of the expedition, large regions with reduced O3 levels were observed by the lidar inside the polar vortex. Ozone had decreased by as much as 17 percent in the center of these areas, and using the in situ measurements made on the ER-2 aircraft, it was concluded that this decline was due to chemical O3 destruction.